Risk Profile of Uterovaginal Prolapse - Pant, Una; Pradhan, R.; Aryal, B. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Pelvic Organ Prolapse is a common problem in Nepal. The aim of this study was to assess the magnitude of pelvic organ prolapse and risk factors associated with it. Methods: This hospital based retrospective descriptive study was conducted in gynecological Out Patient Department of College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan from October 2011 and September 2013.The data were retrieved from the records and analyzed. Women who were earlier subjected for surgical correction of prolapses Cases with pregnancy were excluded from study. Results: There were total 375 cases of genital prolapse out of total 2075 cases of total gynecological admission i.e. 18% incidence. The mean age of patients was 56.79 years with the mean parity of 5.67. 72% cases developed prolapse during their post-menopausal years. Majority of them (84%) lived in hilly area and (57.3%) cases were involved with heavy occupational activities. 50.7% of genital prolapse were from the lower socioeconomic status. Proplase was seen with patients with higher BMI (26-30). Risk factors identified were unsupervised home delivery, rapid succession of pregnancies, and no rest after delivery. Most common clinical presentation of Pelvis Organ Prolapse was mass per vagina (60%). Conclusions: Prolapse is common among rural, farmers, multiparous and post-menopausal women where most of them delivered at home with prolonged labor. Age, low socioeconomic status and heavy manual activities were associated with the prolapse.